2020
DOI: 10.1111/his.14109
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the pattern‐based interpretation of p53 immunohistochemistry as a surrogate for TP53 mutations in vulvar squamous cell carcinoma

Abstract: Aims The most commonly mutated gene in vulvar squamous cell carcinoma (VSCC) is TP53 and its prognostic value, particularly in HPV‐independent VSCC, is uncertain. In other tumours, p53 immunohistochemistry (IHC) is an excellent surrogate marker for TP53 mutations. In order to study this in VSCC, we assigned six p53 IHC patterns into two final classes: ‘wild‐type’ or ‘mutant’. We determined the performance and interobserver variability of this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
69
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(78 citation statements)
references
References 16 publications
8
69
0
1
Order By: Relevance
“…and Kortekaas et al . have demonstrated that p53 IHC is an excellent surrogate for TP53 mutational status when a pattern‐based framework, the same framework that we have used in this study, is used 44,45 . In this pattern‐based framework, there were four mutational IHC patterns [basal overexpression, parabasal/diffuse overexpression, absent (null), and cytoplasmic].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…and Kortekaas et al . have demonstrated that p53 IHC is an excellent surrogate for TP53 mutational status when a pattern‐based framework, the same framework that we have used in this study, is used 44,45 . In this pattern‐based framework, there were four mutational IHC patterns [basal overexpression, parabasal/diffuse overexpression, absent (null), and cytoplasmic].…”
Section: Discussionmentioning
confidence: 99%
“…The low rates of p53 aberrations in dVIN are more likely to be attributable to historically poor reproducibility in diagnosing dVIN and assessing p53 patterns. In the light of recent studies that have directly correlated p53 staining patterns and TP53 mutation status, 44,45 we are able to re‐evaluate the utility of p53 IHC from a new perspective. We recognise, like Liegl et al ., that p53 can be up‐regulated in inflammatory lesions, owing to ischaemic stress resulting from poor oxygenation, vascular alterations, and inflammation 47 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations